(untitled) (Research, Society and Development, 2025)
Obstructive sleep apnea syndrome (OSAS) is a respiratory disorder characterized by recurrent episodes of partial or complete collapse of the upper airway during sleep, leading to intermittent hypoxia and sleep fragmentation, which negatively impact quality of life. This article aims to report on a case of a young, normotensive patient with moderate sleep apnea and a Class II facial pattern associated with mandibular retrognathia. The patient underwent prior orthodontic treatment in preparation for mandibular advancement orthognathic surgery to correct both occlusion and OSAS. The chosen therapeutic approach was based on the presence of facial anatomical abnormalities contributing to OSAS. The gold-standard treatment for OSAS in the literature is continuous positive airway pressure (CPAP); however, due to low adherence, alternative therapeutic approaches have been developed, including orthognathic surgery with bimaxillary advancement. Although CPAP is the first-line treatment for OSAS, orthognathic surgery has proven to be an effective alternative for patients with mandibular retrusion and sleep apnea when appropriately indicated.